Ultrasonic-assisted enzymolysis: Principle and applications. (January 2021) - Umego, Ekene Christopher; He, Ronghai; Ren, Wenbin; Xu, Haining; Ma, Haile
Highlights: Principle and applications of ultrasonic-assisted enzymolysis are reviewed. Ultrasound induces unfolding of proteins to promote proteolysis. Ultrasound assisted enzymolysis enhances synthesis of bioactive peptides. Ultrasound effects on proteins, bioactivity and hydrolysis time. Abstract: Ultrasonic-assisted enzymolysis is the application of ultrasound technology to enhance the process of enzymolysis. Traditional enzymolysis has been met with certain limitations which includes uneven stirring, decreased enzyme activity and protein accumulation as a result of minimal contact between the enzyme and substrate. Ultrasound assisted enzymolysis is based on the potential for cell molecule modification by ultrasound to improve bioavailability of nutrients while retaining the original quality, and the potential use of radical sonochemistry to achieve targeted hydroxylation of polyphenols and carotenoids. The cavitation effects and mechanical action of ultrasound can be advantageous during enzymolysis when applied appropriately. Ultrasound pretreatment of substrates can boost biological activity, alter protein structure, enhance protein conversion rate and accelerate enzyme hydrolysis. This review therefore, explored the principle of ultrasonic-assisted enzymolysis and its effects on protein extraction, biological activity and enzyme hydrolysis as reported by different researchers. Ultrasonic-assisted enzymolysis shows great potentials in enzyme hydrolysis and can be employed as a processing tool by the food and pharmaceutical industries.